2013
DOI: 10.5116/ijme.51f4.f2de
|View full text |Cite
|
Sign up to set email alerts
|

Does personality predict medical students' attitudes to learning communication skills?

Abstract: Objectives: To determine whether personality is related to medical students' attitudes towards learning communication skills and self-ratings on communication skills. Methods: 524 first-and 507 second-year medical students completed the Communications Skills Attitudes Scale and rated their own communication skills. First-year students answered the Eysenck Personality Questionnaire, and second-year students the Zuckerman-Kuhlman Personality Questionnaire. Multiple regression analyses, controlling for gender, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Personality traits also influence students' attitudes towards learning communication skills as Molinvevo and Torrubia (2013) found in their study involving the first year and second year students [13]. Findings showed that students with higher aggression showed worse attitudes.…”
Section: Literature Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…Personality traits also influence students' attitudes towards learning communication skills as Molinvevo and Torrubia (2013) found in their study involving the first year and second year students [13]. Findings showed that students with higher aggression showed worse attitudes.…”
Section: Literature Reviewmentioning
confidence: 85%
“…"It's too much trouble to attend sessions on communication skills" was included in order to remove ambiguity. Questionnaire of this research consisted of 21 items(1,2,3,5,6,7,8,9,10,11,13,14,17,18,19,20, 21, 22, 23, 24 and 25) with two subscales. Ten items represented positive attitudes towards communication skills learning and remaining eleven items represented negative attitudes towards communication skills.…”
mentioning
confidence: 99%
“…However, some studies on academic performance have reported that successful students are generally introverted (Broadbent, 1958;Furneaux, 1957), and Goff and Ackerman (1992) also found a negative relation between extraversion and students' GPA. Molinuevo and Torrubia's (2013) study, which specifically focused on medical students, reported a positive relation between extraversion and learning. Thus, although the literature is not unambiguous, we expected a positive relation for the group of medical physicians:…”
Section: Theory and Hypothesesmentioning
confidence: 92%
“…An added offshoot of this study is the analysis of the direct personality-learning relation, which holds significance in various work settings. It also has implications for the learning of health professionals (Dohetry & Nugent, 2011;Molinuevo & Torrubia, 2013) because systematic investigations are required to test the personalities and learning of health professionals (Ferguson, James, & Madeley, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[12] The literature has demonstrated a correlation between personality and academic success, which supports the consideration of personality traits to better direct students' academic performance. [13][14][15][16] Unfortunately, the primary method of assessing the personality of candidates is through face-to-face interviews, which is a poor practice at best. [1] Therefore, the purpose of this correlational research was to assess the association between the Five Factor Model (FFM) of personality traits and the GPA of students enrolled in a NAP.…”
Section: Introductionmentioning
confidence: 99%